Investment screening and venture capital - Vera Eichenauer; Stefan Köppl; Monika Köppl-Turyna (EcoAustria - Institute for Economic Research, 2024)
In this paper we analyze the effects of investment screening on cross-border venture capital investments in Europe between 2007 and 2022. The data we work with is originally based on PRISM data which has been extended by Eichenauer and Wang and which we combine with deal data from Preqin to assess investment activity. Our results point to unintended negative effects: while the number of actually blocked deals has remained very low, the associated uncertainty and an increase in transaction costs have led to a significant decline in cross-border deals. The effects are stronger in the case of financial (i.e. 'non-strategic') investors, for late-stage venture capital deals, and for deals with investors from non-OECD countries. Moreover, we observe changes in the size of deals and their structure. This has profound policy implications for the financing of innovation in Europe. – – In dieser Arbeit untersuchen wir die Auswirkungen von Investitionsscreenings auf grenzüberschreitende Venture-Capital-Investitionen in Europa zwischen 2007 und 2022. Die zugrunde liegenden Daten basieren auf den PRISM-Daten, die von Eichenauer und Wang erweitert wurden, und wurden mit Deal-Daten von Preqin kombiniert, um die Investitionstätigkeit zu analysieren. Unsere Ergebnisse zeigen unbeabsichtigte negative Effekte: Obwohl die Zahl tatsächlich blockierter Deals sehr gering bleibt, hat die damit verbundene Unsicherheit sowie die Erhöhung der Transaktionskosten zu einem deutlichen Rückgang grenzüberschreitender Investitionen geführt. Besonders stark sind diese Effekte bei finanziellen (d.h. "nicht-strategischen") Investoren, bei späten Venture-Capital-Deals und bei Investoren aus Nicht-OECD-Ländern. Zudem beobachten wir Veränderungen in der Größe und Struktur der Deals. Diese Ergebnisse haben weitreichende politische Implikationen für die Finanzierung von Innovationen in Europa.
Keywords: F55; F21; G24; L14; 330; cross-border venture capital; investment screening; Europe; transaction costs